Menopausa, aspectos psicossociais, sonolência diurna e qualidade de vida em docentes brasileiras: estudo transversal - Masuda, Helen Mami (Universidade Federal de São Carlos, 2023)
Menopause is an important phase in the lives of women, especially those in the job market. The teaching category presents a diversity of demands and high qualification and productivity requirements, which can compromise their physical and mental health. Objective: To associate menopause and psychosocial aspects, daytime sleepiness and quality of life in Brazilian teachers. Methods: This is a cross-sectional study using data from the RESPIRA cohort. Data were collected online using a sociodemographic, occupational and health questionnaire; Copenhagen Psychosocial Questionnaire II-Br; Epworth Sleepiness Scale; WHOQOL-BREF, STOP-Bang and IPAQ-SF. The sample is made up of teachers who work in higher education in Brazilian public educational institutions with an exclusive dedication of 40 hours a week. Data analysis was carried out using descriptive analysis and linear and logistic regression. Results: 411 teachers were included, of which 35.5% reported being in menopause. There was an association between the social relations domain of quality of life (B: -5.15; 95% CI: -9.57 – -0.74), family-work conflicts (OR: 2.10; 95% CI: 1 .20 – 3.68) and burnout (OR: 2.24; 95% CI: 1.07 – 4.69) with menopause. Conclusion: The findings indicate that it is necessary to seek support strategies for teachers in order to improve social relationships, reduce the psychosocial risk related to burnout symptoms and family-work conflicts, necessary to promote better working conditions, as well as quality and quality of life.
Menopause, psychosocial aspects, daytime sleepiness and quality of life in Brazilian teachers: cross-sectional study
Keywords: Menopausa; Sono; Qualidade de vida; Impacto Psicossocial; Saúde do trabalhador; Docentes; OUTROS